Urothelial carcinoma in a Russian tortoise (Testudohorsfieldii). (January 2023) - Hetterich, Johannes; Schmidt, Volker; Herth, Melanie; Merhof, Kristina; Pees, Michael
ABSTRACT: An adult female Russian tortoise ( Testudo horsfieldii ) was admitted to a veterinary clinic with a 1-week history of anorexia and lethargy. Physical examination revealed significant dehydration and generalized dysecdysis. Blood parameters were all within species-reported limits. Radiography revealed an increased amount of soft tissue opacity within the coelomic cavity and a distinct loss of serosal detail. A large cavitated mass was detected ultrasonographically in the right coelom and a tentative diagnosis of kidney pathology was made. Using computed tomography and magnetic resonance imaging, a partly mineralized heterogeneous mass was seen in the right coelom. After stabilization, a transplastron coeliotomy was performed. A 7 × 5 cm mass, including associated cysts, was removed. The tortoise died 8 h postoperatively and post-mortem examination revealed a urothelial carcinoma arising from the renal pelvis. To the authors' knowledge, this is the first report in a tortoise of urothelial carcinoma, which has rarely been reported in reptiles.